The Effectiveness of “Gamilab” Media Online Games For Arabic Vocabulary Mastery at Junior High School - Muhammad Fajar; Miatin Rachmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study explains the effectiveness of teaching Arabic vocabulary mastery using Gamilab media online games, particularly at the junior high school level. The difficulty students face in learning is due to a lack of supportive facilities, which affects their motivation during lessons. This research employs a quantitative approach, with the experimental method used by the researcher. The experimental design follows the